HE IMPLEMENTATION OF MOBILE-ASSISTED EXTENSIVE READING IN SENIOR HIGH SCHOOL (IMPLEMENTASI MEMBACA EKSTENSIF BERBASIS PONSEL DI SEKOLAH MENENGAH ATAS) - Muhammad Andriana Gaffar; Vena Fernanda; Hamdan Hidayat (Balai Bahasa Jawa Barat, 2021)
There is a huge concern among educators about students who are less interested in reading. They are more serious about those who feel bored with reading. It will cause them to feel overwhelmed when given a book or text when asked to analyze or summarize what they have read and cause them to be lazy to read caused by the difficulty to carry books anywhere. Many researchers have tried to find out the reasons behind students' boredom in reading. In an academic context, reading is considered the most important language skill. Through reading, students learn new information.